Peran Kepemimpinan Peratin Terhadap Pembangunan Pekon Tahun 2024 - Veronica Yulia Putri; Nur Islam; Martharia Putri (Fakultas Ilmu Sosial dan Ilmu Poliitik Universitas Ichsan Gorontalo, 2026)
This study aims to examine the leadership role of the village head (Peratin) in the development of Tapak Siring Village (Pekon), Sukau District, West Lampung Regency in 2024. The focus of this research is on the functions of the village head as a motivator, facilitator, and mobilizer in the context of village development. This study employs a descriptive qualitative approach, with data collected through interviews, observations, and documentation. The analytical framework is based on five indicators of the Village Development Index (Indeks Pembangunan Desa/IPD), namely basic services, infrastructure, accessibility, public services, and governance. The results indicate that (1) the village head has made efforts to fulfill these roles; however, their implementation has not been fully optimal due to budget limitations, uneven infrastructure, and limited accessibility to public services, and (2) coordination and communication between the village head and the community remain ineffective, as deliberations involve only hamlet representatives rather than the broader community, alongside insufficient information dissemination and limited community participation in decision-making related to village development. This study concludes that more participatory and strategic leadership is needed to promote sustainable and comprehensive village development.